PHRASEOLOGICAL COMBINATIONS THAT CONTRIBUTE TO THE FORMATION OF THE SCIENTIFIC WORLDVIEW OF SCHOOLCHILDREN - U. E. Ataev (Journals Park Publishing, 2023)
The article discusses phraseological units, their role in speech development, use and understanding. Learning to use phraseological units of the Russian language is considered one of the most difficult tasks for Uzbek schoolchildren. This article shows some ways of using phraseological units in teaching the Russian language, in schools with the Uzbek language of instruction. Currently, in Russian language classes, along with studying phonetics, grammar, vocabulary, and spelling, special attention should be paid to familiarizing students with phraseology. It shows the close connection of language with the life, history and culture of society. In addition, phraseology largely contributes to expanding students ' horizons, deepening their communication skills, and making their speech lively, expressive, and emotional. This creates prerequisites for a higher degree of perception of literary texts. A person who knows the phraseology of their native language, who knows how to use it, usually easily expresses thoughts, as they say "for a word in the pocket does not climb". Studying phraseological units is important for understanding the language and its system.
Keywords: phraseological units, folklore, language, aspects of language, comparison, learning.